2021
DOI: 10.7759/cureus.13155
|View full text |Cite
|
Sign up to set email alerts
|

Double-Expressor Phenotype (BCL-2/c-MYC Co-expression) of Diffuse Large B-Cell Lymphoma and Its Clinicopathological Correlation

Abstract: Introduction Diffuse large B-cell lymphoma (DLBCL) is a heterogeneous disease, the spectrum of which is increasing with time. The 2016 World Health Organization (WHO) update on hematopoietic tumors recognized a prognostic subgroup of DLBCL called double-expressor DLBCL. Double-expressor DLBCL is defined by the coexpression of c-MYC and BCL-2 by using immunohistochemical (IHC) studies. To our knowledge, very few studies have looked into the pathological features of this newly defined prognostic category of DLBC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…On the other part, DLBCL cases with low CISD2Risk value were often obtained a curative treatment ( P < 0.05, Figures 5K ). Several studies revealed the poor prognosis of MYC and BCL2 and/or BCL6 overexpression in DLBCL, known as double-expressor DLBCL ( 21 , 42 ). We also reported the overexpression of MYC and BCL2 in DLBCL cases were possiblely associated with CISD2Risk value, and the double-expressor DLBCL exhibited the high CISD2Risk value ( P < 0.05, Figure 5L ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other part, DLBCL cases with low CISD2Risk value were often obtained a curative treatment ( P < 0.05, Figures 5K ). Several studies revealed the poor prognosis of MYC and BCL2 and/or BCL6 overexpression in DLBCL, known as double-expressor DLBCL ( 21 , 42 ). We also reported the overexpression of MYC and BCL2 in DLBCL cases were possiblely associated with CISD2Risk value, and the double-expressor DLBCL exhibited the high CISD2Risk value ( P < 0.05, Figure 5L ).…”
Section: Resultsmentioning
confidence: 99%
“…In this study, the MHG DLBCL patients exhibited highest CISD2Risk value which indicated a poor prognosis. MHG DLBCL has distinct molecular features with concurrent activation of MYC and BCL2 ( 21 , 42 ). DLBCL patients with double-expressor that defined by the coexpression of MYC and BCL-2 have a poor prognosis after standard chemoimmunotherapy ( 21 , 42 ).…”
Section: Discussionmentioning
confidence: 99%
“…The non-GCB subtype (including ABC) are either double negative for CD10 and BCL6 or positive for both BCL6 and MUM1. Positivity for both BCL2 and MYC on IHC classifies it as double expressor DLBCL, seen in about 30% of DLBCL, NOS cases [52]. Positivity is defined as >30% cells expressing the marker.…”
Section: Large Cell Lymphoma (Burkitt Lymphoma) Dirty Proteinaceous B...mentioning
confidence: 99%
“…Inferior and insufficient response to both standard first line therapy [19,21] and in relapsed/refractory settings [9,22] have been observed. In addition, DEL phenotype is associated significantly with the female gender, older age, higher Ki-67 [23], elevated LDH level [24], poor performance status, higher IPI score and higher incidence of extranodal sites [25]. Treatment intensification in first line settings is a matter of debate and controversy, raising questions and confusion between clinicians.…”
Section: Clinical Implication Of Double Expressor Lymphomas and Treat...mentioning
confidence: 99%